Grass composition and distribution patterns as determinants of behavioral activities and weight accumulation of Nguni and Boran cattle post-relocation - Slayi, Mhlangabezi; Zhou, Leocadia; Njisane, Yonela Zifikile (Frontiers in Veterinary Science, 2022)
Grass biomass composition and distribution patterns within the paddock as determinants of behavioural activities and animal performance of Nguni (NG) and Boran (BR) cattle post relocation to a novel environment were examined. Ten steers of each breed aged 9 months were bought from two different farms and sent to Honeydale research facilities where they were reared on rangelands for 12-weeks. Identification and classification of grass species was done every sampling week prior introducing cattle to each paddock. Direct visual observations and durations of behavior and paddock occupancy patterns were recorded every fortnight between 0500-1900h every week. Individual animal weights and body condition scores were recorded twice per week. Location within paddocks hugely affected (P<0.0001) the composition of the vegetation as most grass species were found everywhere on pastures, near the watering points and along fencelines. However, the distribution patterns of the grass species significantly differed at different locations. Aristida congesta was dominant (P=0.0014) everywhere in the pasture and along fenceline than in areas with high density of trees. Except in shaded areas, Cynodon dactylon (P=0.0003) and Eragrostis chloromelas (P=0.0008) were highly abundant near the watering points, pastures and along fenceline. Themeda triandra (P<0.0001) was only prevalent everywhere on pastures except on shade areas, near the water sites and along fenceline. In terms of palatability and ecological groups, highly palatable species (P<0.0001) and decreasers (P=0.0010) were more frequent everywhere in the paddocks. From week 1-3, NG spent more time walking (P<0.0001), while the BR showed a significant decline in grazing activities (P<0.0001) inspite of several differences in vegetation composition. Both breeds showed a significant decline in weight gain (P<0.0001) and body condition score (P<0.0001) in the first three weeks. However, the two cattle breeds quickly compensated their behavioral activities and weight gain and this show good ability to cope with stress caused by heterogenous environmental conditions.